[Alvar Aalto] : [Selected Buildings and Projects] (1978)
Contiene: Workers´Club 1924 - Civil Guard Buildings 1925 - Municipal Library 1927-1935 - Sanatorium and Housing 1929-1933 - University Library Extension Competition 1937 - Library, Institute of Technology 1964-1969 - Library 1963-1965 - Library 1963-1968 - Library, Mount Angel Benedictine College 1965-1970 - Academic Bookshop Competition 1962 Constructed 1969 - Block of Flats 1965-1968 - Architect´s Studio 1953-1956 - Architect´s House 1953 - Lappia House 1975 - Central Finland Museum 1959-1962 - Town Hall Competition 1949 Completed 1952 - National Pensions Building Competition 1949 Completed 1952 - Otaniemi Institute of Technology, Main Buildings Competition 1949 Completion 1964 - Cultural Centre Competition 1958 Construction 1959-1963 - Students´Hostel Otaniemi Institute of Technology 1962-1966.
Keywords: AALTO, ALVAR; FINLANDIA; RUSIA; USA; ESTADOS UNIDOS; SUIZA; ALEMANIA; WOLFSBURG; HELSINKI; OREGON; ARQUITECTURA DEPORTIVA; ARQUITECTURA MILITAR; ARQUITECTURA HOSPITALARIA; BIBLIOTECAS; BIBLIOTECAS UNIVERSITARIAS; BIBLIOTECAS PUBLICAS; SANATORIOS; CUARTELES MILITARES; CLUBES; CLUBES SOCIALES; INSTITUTOS; VIVIENDAS PARA ARQUITECTOS; VIVIENDAS UNIFAMILIARES; MUSEOS; MUNICIPALIDADES; CENTROS TECNOLOGICOS; CENTROS CULTURALES; RESIDENCIAS ESTUDIANTILES; ALBERGUES; CONCURSOS; LADRILLO; HORMIGON; MADERA